A novel decision making method for two-way referral based on SMAA-2 and two-sided matching model. (17th February 2018) - Wang, Jin; Li, Wei; Chen, Yi; Li, Bo; Yang, Shan-Lin
Abstract: In the background of hierarchical diagnosis and treatment, the problems of two-way referral have attracted considerable attention in recent years. Most research of two-way referral mainly focuses on the qualitative research on the operation mechanism and the management mode, but there arefew considerations of decision making method for two-way referral. In this paper, we use stochastic multicriteria acceptability analysis-2 (SMAA-2) to solve the problem of uncertainties of indicator values and weights in two-sided matching decision-making for two-way referral.